2022
DOI: 10.3389/fpls.2022.923183
|View full text |Cite
|
Sign up to set email alerts
|

Integrative mRNA and Long Noncoding RNA Analysis Reveals the Regulatory Network of Floral Bud Induction in Longan (Dimocarpus longan Lour.)

Abstract: Longan (Dimocarpus longan Lour.) is a tropical/subtropical fruit tree of significant economic importance. Floral induction is an essential process for longan flowering and plays decisive effects on the longan yield. Due to the instability of flowering, it is necessary to understand the molecular mechanisms of floral induction in longan. In this study, mRNA and long noncoding RNA (lncRNA) transcriptome sequencing were performed using the apical buds of fruiting branches as materials. A total of 7,221 differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…There are various mechanisms for the lncRNA regulation of target genes, and the most common forms of regulation are cis and trans regulation [ 47 ]. Based on the results of RNA-seq, we predicted the target genes for the differentially expressed lncRNAs in cis and trans regulation.…”
Section: Discussionmentioning
confidence: 99%
“…There are various mechanisms for the lncRNA regulation of target genes, and the most common forms of regulation are cis and trans regulation [ 47 ]. Based on the results of RNA-seq, we predicted the target genes for the differentially expressed lncRNAs in cis and trans regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified a significantly correlated module based on a correlation coefficient (r) ≥ 0.9 and p < 0.01. The coexpression networks of lncRNAs and hub lncRNAs in highly correlated modules were generated with the Cytoscape software (version 3.7.1) [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…org). The conservation analysis of lncRNAs was assessed using the E-value, where a threshold of E-value <1x10 -5 was used (24). After conservation analysis among species (Table IV…”
Section: Characteristics Of Differentially Expressed Lncrnasmentioning
confidence: 99%